Nanometer multilayer nitride coating, cutter and preparation method
Through the nano-multi-layer nitride coating process of alternating deposition of AlCrN and MeSiN layers, the problems of large surface particles in arc ion plating technology are solved, the density and smoothness of the tool coating are improved, and the service life is extended And improve the carrying capacity.
Patent Information
- Application Number
- CN202411136338.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2024-12-13
AI Technical Summary
Arc ion plating technology is difficult to reduce the density and roughness of large surface particles when depositing hard tool coatings, affecting the performance and life of the coating.
Using an alternating deposition nano-multilayer nitride coating process, the AlCrN and MeSiN layers are deposited by adjusting the air pressure, temperature and arc targets in the coating chamber, and the grain structure is refined to improve density and smoothness.
It significantly improves the density and smoothness of the coating, extends the service life, and improves the bearing capacity of the coating under harsh working conditions.
Smart Images

Figure CN119121125A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of coating preparation, and in particular to a nano multilayer nitride coating, a cutting tool and a preparation method. Background Art
[0002] In recent years, advanced manufacturing technology (ultra-precision machining, high-speed machining, etc.) has developed rapidly, which has put forward higher requirements for modern cutting technology. Faster cutting speed, feed speed, longer service life, and higher precision and stability are the development direction of modern cutting technology. However, when cutting some difficult-to-process materials (die steel, titanium alloy, stainless steel and high-temperature alloy, etc.), the high cutting temperature makes the tool very easy to cause problems such as chipping, wear, sticking, oxidation, etc., which greatly reduces the quality and efficiency of cutting processing. Therefore, it is very important to have a smooth surface and edge of the tool with less adhesion.
[0003] Arc ion plating technology is a commonly used technology for preparing cutting tool coatings. The ionization rate is as high as nearly 100%. The coating has strong adhesion, high hardness, and good wear resistance. In addition, the coating equipment cost is low and the coating cost-effective. It shows unparalleled advantages in the application of cutting tool industry.
[0004] However, arc ion plating also has its inherent disadvantages. When the arc source target evaporates, it will inevitably splash out a certain number of target droplets of a certain size. These droplets will eventually form macroscopic particles (MP) on the surface of the film. The presence of these particles greatly affects the smoothness of the film surface and increases the friction coefficient. Moreover, the droplet particles will produce holes and loose defects in the arc ion plating coating. These defects exist within the crystal, at the grain boundary or throughout the entire coating. The presence of defects greatly affects the performance of the coating.
[0005] Although magnetic filtration technology can filter out most of the droplet particles, since most of the plasma beam is filtered, the coating deposition rate is extremely low, making it difficult for magnetic filtration arc technology to meet the requirements in terms of performance and cost in the preparation of hard tool coatings. Therefore, how to reduce the density of large particles and surface roughness when depositing hard tool coatings with arc ion plating technology is crucial to its application. The degree to which the performance and life of tool coatings deposited with arc ion plating technology are affected by arc particles is closely related to the target material composition and specific process parameters.
[0006] AlCrN coating has been widely used as tool coating due to its excellent hardness and high temperature stability. The Al element in the coating enables the coating to form a dense aluminum oxide protective film at high temperatures of high-speed cutting, which can effectively increase the oxidation resistance of the coating. The high red hardness of the AlCrN coating enables it to maintain stable performance under extremely high thermal loads. Therefore, the processing performance of AlCrN coated tools is better than that of other types of coated tools, especially under high-speed cutting and dry (or quasi-dry) cutting conditions.
[0007] However, the large number of droplets and large particles on the coating surface is the key disadvantage of arc ion plating technology deposited AlCrN coating, which greatly affects the performance and application of arc ion plating AlCrN coating. Therefore, in order to adapt to the development of advanced cutting technology and the requirements of high-speed and high-efficiency cutting, it is imperative to seek methods to improve the surface smoothness of arc ion plating AlCrN coating and improve the cutting application performance. Summary of the invention
[0008] In order to solve at least one of the above technical problems, the present application provides a nano multilayer nitride coating, a tool and a preparation method, and the technical solution adopted is as follows.
[0009] The preparation method provided in the present application obtains a nano multilayer nitride coating by alternate deposition, and the preparation method includes the following process flow:
[0010] Pre-treating the substrate;
[0011] Inert gas and nitrogen are introduced into the coating chamber, the partial pressure of the inert gas is 0.3 to 0.5 Pa, and the gas pressure in the coating chamber is 1.2 to 3.0 Pa;
[0012] Adjust the substrate bias voltage to -100 to -300 V, the temperature to 300 to 600 ° C, turn on the cathode arc AlCr target and cathode arc MeSi target, Me is Ti or AlTi, and adjust the average current density of the arc target to 0.5 to 1.5 A / cm 2 ;
[0013] AlCrN layers and MeSiN layers are alternately deposited on the substrate, with a deposition time ranging from 180 to 300 min.
[0014] In certain embodiments of the present application, in the cathode arc AlCr target, the Al content is 50 to 70 at.%, and the Cr content is 30 to 50 at.%.
[0015] In certain embodiments of the present application, if Me is Ti, the Si content in the TiSi target is 10 to 20 at.%; or, if Me is AlTi, the Si content in the AlTiSi target is 10 to 20 at.%, and the Al / Ti atomic ratio is 1:1 to 2:1.
[0016] In certain embodiments of the present application, after the substrate is placed in the coating chamber, an inert gas is introduced into the coating chamber, the gas pressure of the coating chamber is set to 2Pa, the substrate bias voltage is -1000V, and the coating chamber is glow sputtered for cleaning for 30 minutes; the substrate bias voltage is adjusted to -800V, the gas pressure is adjusted to 0.5Pa, the cathode arc Cr target is turned on, the target current is 80A, and the substrate is ion etched for 5 minutes.
[0017] In certain embodiments of the present application, the substrate is made of cemented carbide.
[0018] The nano multilayer nitride coating provided in the present application is deposited by the preparation method as described above, and the nano multilayer nitride coating includes AlCrN layers and MeSiN layers that are periodically and alternately deposited.
[0019] In certain embodiments of the present application, the nano-multilayer nitride coating comprises 300 to 500 cycles, and the thickness of the nano-multilayer nitride coating is 3.5 to 4.5 μm.
[0020] In some embodiments of the present application, within one period, the thickness of the AlCrN layer is 4 to 6 nm, and the thickness of the MeSiN layer is 5 to 15 nm.
[0021] In certain embodiments of the present application, the nano multilayer nitride coating is deposited on the surface of a tool, and the tool is applied to mechanical processing, and the mechanical processing includes at least one of turning, milling, drilling, boring and grinding.
[0022] The surface of the tool provided in the present application is deposited with the aforementioned nano multilayer nitride coating, and the material of the tool is one of high-speed steel, cemented carbide, metal ceramic, ceramic and cubic boron nitride.
[0023] The present application has at least the following beneficial effects: in the present application, a nano-multilayer nitride coating is obtained by alternately depositing AlCrN layers and MeSiN layers, which refines the grain structure of the coating, improves the density and surface smoothness of the coating, extends the service life of the coating, and can also increase the coating thickness without passivating the tool edge, thereby improving the bearing capacity of the coating under harsh working conditions.
[0024] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The present application is further illustrated below in conjunction with the accompanying drawings and embodiments. It should be noted that the embodiments embodied in the following drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.
[0026] Figure 1This is a structural principle diagram of the high-density, high-smoothness arc ion-plated AlCrN / MeSiN hard coating in this application, in which the inserted elliptical particles are a schematic diagram of the growth of large arc molten droplet particles in the coating.
[0027] Figure 2 The following is a comparison of the surface morphologies of Comparative Example 1, Comparative Example 2 and Example 1, Example 2 under a scanning electron microscope.
[0028] Figure 3 The figure is a comparison of the fracture cross-sectional morphologies of Comparative Example 1, Comparative Example 2 and Example 1, Example 2 under a scanning electron microscope.
[0029] Figure 4 The figure is a comparison of the tool edge morphologies of Comparative Example 1, Comparative Example 2 and Example 1, Example 2 under a scanning electron microscope.
[0030] Figure 5 For the cutting performance comparison between comparative examples 1 and 2 and embodiment 1, the cutting method is turning, the processed material is SKD11 die steel, the cutting line speed is 100 m / min, the feed is 0.2 mm / r, and the cutting depth is 0.5 mm. DETAILED DESCRIPTION
[0031] The embodiments of the present application are described in detail below in conjunction with the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.
[0032] In the description of the present application, it should be understood that the terms "center", "middle", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0033] In the description of this application, "several" means more than one, "more" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, and "above", "below", "within", etc. are understood to include the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0034] In the description of this application, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense, for example: it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0035] In the description of the present application, if the reference terms "as an implementation", "an embodiment", "some instances", "some embodiments", "illustrative embodiment", "example", "specific example", "some examples", etc. appear, it means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0036] The application relates to a cutting tool, the surface of which is deposited with a nano multilayer nitride coating.
[0037] The tool is made of one of high speed steel, cemented carbide, cermet, ceramic and cubic boron nitride.
[0038] The other components and operations of the tool are already documented in the relevant technologies for ordinary technicians in this field and will not be described in detail here. The structure and preparation method of the nano multilayer nitride coating will be introduced below.
[0039] The present application relates to a nano multilayer nitride coating, which is obtained by alternate deposition and has high density and high smoothness. The nano multilayer nitride coating comprises periodically alternately deposited AlCrN layers and MeSiN layers.
[0040] The nano-multilayer nitride coating includes 300 to 500 cycles, and the thickness of the nano-multilayer nitride coating is 3.5 to 4.5 μm.
[0041] In one cycle, the thickness of the AlCrN layer is 4 to 6 nm, and the thickness of the MeSiN layer is 5 to 15 nm. The performance of the nano multilayer structure coating is closely related to its modulation period (the sum of the thickness of a single AlCrN layer and a single MeSiN layer). The thickness range of the AlCrN layer and the MeSiN layer designed in this application can combine the respective advantages of the two nitrides to improve the mechanical properties of the coating and improve the wear resistance of the tool surface.
[0042] It should be noted that the nano multilayer nitride coating is deposited on the surface of the tool, and the tool is used for mechanical processing, and the mechanical processing includes at least one of turning, milling, drilling, boring and grinding.
[0043] The present application relates to a preparation method, wherein the preparation method deposits a coating by arc ion plating, and obtains a nano multilayer nitride coating by alternate deposition.
[0044] The present application prepares a nano multilayer nitride coating by alternately depositing AlCrN layers and MeSiN layers. The prepared coating has good comprehensive mechanical properties and film-base bonding strength, can achieve the alternating nano multilayer growth of AlCrN layers and MeSiN layers, refines the overall grain structure of the coating, improves the density and surface smoothness of the coating, and prolongs the service life of the coating. It can also increase the coating thickness without passivating the cutting edge of the tool, thereby improving the bearing capacity of the coating under harsh working conditions.
[0045] The process flow of the preparation method includes the following steps.
[0046] S1, pre-treating the substrate.
[0047] S2, introducing inert gas and nitrogen into the coating chamber, the partial pressure of the inert gas is 0.3 to 0.5 Pa, and the gas pressure in the coating chamber is 1.2 to 3.0 Pa.
[0048] S3, adjust the substrate bias voltage to -100 to -300 V, the temperature to 300 to 600 ° C, turn on the cathode arc AlCr target and cathode arc MeSi target, Me is Ti or AlTi, and adjust the average current density of the arc target to 0.5 to 1.5 A / cm 2 .
[0049] S4, AlCrN layers and MeSiN layers are alternately deposited on the substrate, and the deposition time is 180 to 300 minutes.
[0050] It should be noted that the substrate is made of cemented carbide.
[0051] In step S1, the substrate is placed on a rotating rack in the coating chamber, the rotating rack is set to a revolution speed of 0.5 rpm and a rotation speed of 3 rpm, the coating chamber is heated to 500°C, and the background vacuum is pre-evacuated to 4*10 -3 Pa.
[0052] After the substrate is placed in the coating chamber, an inert gas is introduced into the coating chamber, the gas pressure of the coating chamber is set to 2Pa, the substrate bias is set to -1000V, and the coating chamber is glow sputtered for 30min. The substrate bias is adjusted to -800V, the gas pressure is adjusted to 0.5Pa, the cathode arc Cr target is turned on, the target current is 80A, and the substrate is ion etched for 5min.
[0053] In steps S1 and S2, argon is used as the inert gas.
[0054] In step S3, in the cathode arc AlCr target, the Al content is 50 to 70 at.%, and the Cr content is 30 to 50 at.%.
[0055] In step S3, the average current density of the arc target is 0.5 to 1.5 A / cm 2 , ensuring that the thickness of the AlCrN layer and the MeSiN layer are controllable.
[0056] In step S3, if Me is Ti, the Si content in the TiSi target is 10 to 20 at.%. If Me is AlTi, the Si content in the AlTiSi target is 10 to 20 at.%, and the Al / Ti atomic ratio is 1:1 to 2:1. If the Si content is too low, the mechanical and oxidation resistance of the prepared TiSiN or AlTiSiN layer is too low. If the Si content is too high, the TiSiN or AlTiSiN layer is prone to excessive amorphous structures, which is not conducive to the formation of epitaxially grown nano multilayer structures. If the Al content is too low, the oxidation resistance of the AlTiSiN layer is poor. If the Al content is too high, the AlTiSiN layer is prone to hexagonal AlN phase, which will damage the overall mechanical properties of the coating.
[0057] In step S4, the TiSiN or AlTiSiN coating obtained by cathode arc MeSi target deposition has a great difference in performance compared with the AlCrN coating. The TiSiN or AlTiSiN coating has a large lattice constant and can obtain a large interlayer coherence distortion when forming epitaxial growth with AlCrN, which is helpful to improve the mechanical properties of the coating. Selecting two nitrides with different properties is conducive to combining the advantages of both through the construction of a nano multilayer structure.
[0058] The MeSiN layer is a fine nanocrystalline structure. When the MeSiN layer is added to the coating, the columnar crystal growth of the AlCrN layer is interrupted, so that the coating structure changes from an obvious columnar crystal structure to a fine crystal structure, and the growth of large droplet particles is blocked. The coating has excellent high density and high smoothness, thereby improving the cutting performance of the coating.
[0059] The contents of the present application are described in detail below in conjunction with specific embodiments. It should be noted that the following description is only for illustrative purposes and is not a specific limitation to the present application.
[0060] Example 1
[0061] S1, pre-treat the substrate, place the substrate on a rotating rack in the coating chamber, set the rotating rack's revolution speed to 0.5 rpm, the rotation speed to 3 rpm, heat the coating chamber to 500°C, pre-evacuate the background vacuum to 4*10 -3Pa.
[0062] Argon gas was introduced into the coating chamber, the gas pressure in the coating chamber was set to 2 Pa, the substrate bias voltage was set to -1000 V, and the coating chamber was glow sputtered for cleaning for 30 minutes.
[0063] The substrate bias voltage was adjusted to -800 V, the gas pressure was adjusted to 0.5 Pa, the cathode arc Cr target was turned on, the target current was 80 A, and the substrate was ion etched for 5 minutes.
[0064] S2, reduce the substrate bias voltage to -100V, the argon partial pressure to 0.3Pa, and then pass nitrogen, and the total gas pressure in the coating chamber is set to 1.6Pa.
[0065] S3, adjust the substrate bias voltage to -100 V, the coating chamber temperature to 350 ° C, turn on the cathode arc AlCr target and cathode arc AlTiSi target, and adjust the average current density of the arc target to 1 and 1.2 A / cm 2 .
[0066] S4, AlCrN layers and AlTiSiN layers are alternately deposited on the substrate, and the deposition time is 180 min.
[0067] Among them, in the cathode arc AlCr target, the Cr content is 30at.%, and the Al content is 70at.%. In the cathode arc AlTiSi target, the Si content is 10at.%, the Al content is 30at.%, and the Ti content is 60at.%.
[0068] The obtained high-density and high-smooth AlCrN / AlTiSiN nano-multilayer hard coating has a thickness of 4 μm.
[0069] Example 2
[0070] S1, pre-treat the substrate, place the substrate on a rotating rack in the coating chamber, set the rotating rack's revolution speed to 0.5 rpm, the rotation speed to 3 rpm, heat the coating chamber to 500°C, pre-evacuate the background vacuum to 4*10 -3 Pa.
[0071] Argon gas was introduced into the coating chamber, the gas pressure in the coating chamber was set to 2 Pa, the substrate bias voltage was set to -1000 V, and the coating chamber was glow sputtered for cleaning for 30 minutes.
[0072] The substrate bias voltage was adjusted to -800 V, the gas pressure was adjusted to 0.5 Pa, the cathode arc Cr target was turned on, the target current was 80 A, and the substrate was ion etched for 5 minutes.
[0073] S2, reduce the substrate bias voltage to -100V, the argon partial pressure to 0.3Pa, and then pass nitrogen, and the total gas pressure in the coating chamber is set to 1.6Pa.
[0074] S3, adjust the substrate bias voltage to -100 V, the coating chamber temperature to 350 ° C, turn on the cathode arc AlCr target and cathode arc TiSi target, and adjust the average current density of the arc target to 1 and 1.2 A / cm 2 .
[0075] S4, AlCrN layers and TiSiN layers are alternately deposited on the substrate, and the deposition time is 180 min.
[0076] Among them, in the cathode arc AlCr target, the Cr content is 30at.%, and the Al content is 70at.%. In the cathode arc TiSi target, the Si content is 15at.%, and the Ti content is 85at.%.
[0077] The obtained high-density and high-smooth AlCrN / TiSiN nano-multilayer hard coating has a thickness of 4 μm.
[0078] Comparative Example 1
[0079] S1, pre-treat the substrate, place the substrate on a rotating rack in the coating chamber, set the rotating rack's revolution speed to 0.5 rpm, the rotation speed to 3 rpm, heat the coating chamber to 500°C, pre-evacuate the background vacuum to 4*10 -3 Pa.
[0080] Argon gas was introduced into the coating chamber, the gas pressure in the coating chamber was set to 2 Pa, the substrate bias voltage was set to -1000 V, and the coating chamber was glow sputtered for cleaning for 30 minutes.
[0081] The substrate bias voltage was adjusted to -800 V, the gas pressure was adjusted to 0.5 Pa, the cathode arc Cr target was turned on, the target current was 80 A, and the substrate was ion etched for 5 minutes.
[0082] S2, reduce the substrate bias voltage to -100V, the argon partial pressure to 0.3Pa, and then pass nitrogen, and the total gas pressure in the coating chamber is set to 1.6Pa.
[0083] S3, adjust the substrate bias voltage to -100V, the coating chamber temperature to 350℃, turn on the cathode arc AlCr target, and adjust the average current density of the AlCr target to 1A / cm 2 , an AlCrN layer was deposited on the cemented carbide substrate, and the deposition time was 90 min.
[0084] Among them, in the cathode arc AlCr target, the Cr content is 30at%, and the Al content is 70at%.
[0085] The obtained AlCrN hard coating has a thickness of 4.0 μm, an Al content of 28.6 at %, a Cr content of 16.8 at %, and a N content of 54.6 at %.
[0086] Comparative Example 2
[0087] S1, pre-treat the substrate, place the substrate on a rotating rack in the coating chamber, set the rotating rack's revolution speed to 0.5 rpm, the rotation speed to 3 rpm, heat the coating chamber to 500°C, pre-evacuate the background vacuum to 4*10 -3 Pa.
[0088] Argon gas was introduced into the coating chamber, the gas pressure in the coating chamber was set to 2 Pa, the substrate bias voltage was set to -1000 V, and the coating chamber was glow sputtered for cleaning for 30 minutes.
[0089] The substrate bias voltage was adjusted to -800 V, the gas pressure was adjusted to 0.5 Pa, the cathode arc Cr target was turned on, the target current was 80 A, and the substrate was ion etched for 5 minutes.
[0090] S2, reduce the substrate bias voltage to -100V, adjust the flow rate of argon and nitrogen, the argon partial pressure is 0.3Pa, and then pass nitrogen, the total gas pressure in the coating chamber is set to 1.6Pa.
[0091] S3, adjust the substrate bias voltage to -100V, the coating chamber temperature to 350℃, turn on the cathode arc AlTiSi target, and adjust the average current density of the AlTiSi target to 1.2A / cm 2 , an AlTiSiN layer was deposited on the cemented carbide substrate, and the deposition time was 120 min.
[0092] Among them, in the cathode arc AlTiSi target, the Si content is 10at.%, the Al content is 30at.%, and the Ti content is 60at.%.
[0093] The obtained AlTiSiN hard coating has a thickness of 3.8 μm, an Al content of 30.8 at %, a Ti content of 16.6 at %, a Si content of 9.5 at %, and a N content of 43.1 at %.
[0094] It should be noted that in each embodiment and comparative example, the deposition time is controlled respectively so that the thickness of each coating obtained is close.
[0095] Combined with Figure 2 -Attached Figure 4 , Figure 2 a. Figure 3 a. Figure 4 a is the cathode arc deposited AlCrN coating obtained in Comparative Example 1, Figure 2 b. Figure 3 b. Figure 4 b is the cathode arc deposited AlTiSiN coating obtained in Comparative Example 2, Figure 2 c. Figure 3 c. Figure 4c is the cathode arc deposited AlCrN / AlTiSiN nano multilayer coating of Example 1, Figure 2 d. Figure 3 d. Figure 4 d is the cathode arc deposited AlCrN / TiSiN nano multilayer coating of Example 2.
[0096] Among them, the coating obtained in comparative example 1 presents an obvious columnar crystal structure, and there are more large particles on the surface of the coating and the surface of the tool edge, and the surface is relatively rough. The coating obtained in comparative example 2 has grain refinement due to the Si element, so that the cross section of the coating presents a fine-grained structure of a glass-like phase, and the particles on the surface of the coating are reduced, but still relatively large, which affects the roughness of the coating surface and the tool edge. The coatings of Example 1 and Example 2 are fine nano-grains, with dense structures, fewer large particle defects in the middle and surface of the coating, and the coating surface and the tool edge are smooth and dense, which is conducive to improving the life of the coating.
[0097] Combined with Figure 5 , are the flank wear curves of the turning tools coated with comparative example 1, comparative example 2 and embodiment 1 when cutting SKD11 high-hardness difficult-to-machine material. It can be seen that compared with comparative example 1 and comparative example 2, the AlCrN / AlTiSiN nano multilayer coating of embodiment 1 has a greatly improved cutting life due to the densification of the structure and the smoothness of the coating surface and the cutting edge.
[0098] The above is a detailed description of the implementation methods of the present application in conjunction with the accompanying drawings, but the present application is not limited to the above implementation methods. Various changes can be made within the knowledge of ordinary technicians in the technical field without departing from the purpose of the present application. In addition, the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
Claims
1. A preparation method, characterized in that: The preparation method obtains a nano multilayer nitride coating by alternate deposition. The preparation method comprises Pre-treating the substrate; Inert gas and nitrogen are introduced into the coating chamber, the partial pressure of the inert gas is 0.3 to 0.5 Pa, and the gas pressure in the coating chamber is 1.2 to 3.0 Pa; Adjust the substrate bias voltage to -100 to -300 V, the temperature to 300 to 600 ° C, turn on the cathode arc AlCr target and cathode arc MeSi target, Me is Ti or AlTi, and adjust the average current density of the arc target to 0.5 to 1.5 A / cm 2 ; AlCrN layers and MeSiN layers are alternately deposited on the substrate, with a deposition time ranging from 180 to 300 min.
2. The preparation method according to claim 1, characterized in that: In the cathodic arc AlCr target, the Al content is 50 to 70 at.%, and the Cr content is 30 to 50 at.%.
3. The preparation method according to claim 1, characterized in that: If Me is Ti, the Si content in the TiSi target is 10 to 20 at. %; or, if Me is AlTi, the Si content in the AlTiSi target is 10 to 20 at. %, and the Al / Ti atomic ratio is 1:1 to 2:
1.
4. The preparation method according to any one of claims 1 to 3, characterized in that: After the substrate is placed in the coating chamber, inert gas is introduced into the coating chamber, the gas pressure of the coating chamber is set to 2Pa, the substrate bias is -1000V, and the coating chamber is glow sputtered for cleaning for 30 minutes; the substrate bias is adjusted to -800V, the gas pressure is adjusted to 0.5Pa, the cathode arc Cr target is turned on, the target current is 80A, and the substrate is ion etched for 5 minutes.
5. The preparation method according to claim 1, characterized in that: The substrate is made of cemented carbide.
6. A nano multilayer nitride coating, characterized in that: The nano-multilayer nitride coating is deposited by the preparation method according to any one of claims 1 to 5, and the nano-multilayer nitride coating comprises AlCrN layers and MeSiN layers that are periodically and alternately deposited.
7. The nano multilayer nitride coating according to claim 6, characterized in that: The nano-multilayer nitride coating comprises 300 to 500 cycles, and the thickness of the nano-multilayer nitride coating is 3.5 to 4.5 μm.
8. The nano multilayer nitride coating according to claim 7, characterized in that: In one period, the thickness of the AlCrN layer is 4 to 6 nm, and the thickness of the MeSiN layer is 5 to 15 nm.
9. The nano multilayer nitride coating according to any one of claims 6 to 8, characterized in that: The nano multilayer nitride coating is deposited on the surface of a tool, and the tool is used for mechanical processing, and the mechanical processing includes at least one of turning, milling, drilling, boring and grinding.
10. A cutting tool, characterized in that: The surface of the tool is deposited with the nano multilayer nitride coating as claimed in any one of claims 6 to 9, and the material of the tool is one of high-speed steel, cemented carbide, metal ceramic, ceramic and cubic boron nitride.
Citation Information
Patent Citations
Multilayered coated cutting tool
CN101209611A
Multilayer nanometer composite cutting tool coating and preparation method thereof
CN104131256A
Nano composite cutting tool coating of multilayer structure
CN105112858A
Superhard tool surface composite hard coating and preparing method thereof
CN105543780A
AlCrN / AlCrSiN superhard nano-composite laminated coating and preparation method and application of AlCrN / AlCrSiN superhard nano-composite laminated coating
CN109161841A
